Evidence of AGN-driven Outflows in Young Radio Quasars Selected from the Wide-field Infrared Survey Explorer. Issue Volume 9:Issue S304(2013) (25th July 2014) - Kim, Minjin; Ho, Luis C.; Lonsdale, Carol J.; Lacy, Mark; Blain, Andrew W.; Kimball, Amy E.
Abstract: We present near-infrared spectra of young radio quasars selected by cross-correlating the Wide-field Infrared Survey Explorer (WISE) all-sky survey catalog with the radio catalog [Faint Images of the Radio Sky at Twenty cm (FIRST) and NRAO VLA Sky Survey (NVSS)]. The objects have typical redshifts of z ≈ 2 and [O III] luminosities of 10 7 erg s −1 comparable to those of luminous quasars. The observed flux ratios of narrow emission lines indicate that these objects appear to be powered by active galactic nuclei. The [O III] line is broad, with full width at half maximum 1300 to 2100 km s −1, significantly larger than that of ordinary quasars. These large line widths might be explained by jet-induced outflows.